Diastolic Backward-Traveling Decompression (Suction) Wave Correlates With Simultaneously Acquired Indices of Diastolic Function and Is Reduced in Left Ventricular Stunning. (September 2016) - Ladwiniec, Andrew; White, Paul A.; Nijjer, Sukhjinder S.; O'Sullivan, Michael; West, Nick E.J.; Davies, Justin E.; Hoole, Stephen P.
Abstract : Background—: Wave intensity analysis can distinguish proximal (propulsion) and distal (suction) influences on coronary blood flow and is purported to reflect myocardial performance and microvascular function. Quantifying the amplitude of the peak, backwards expansion wave (BEW) may have clinical utility. However, simultaneously acquired wave intensity analysis and left ventricular (LV) pressure–volume loop data, confirming the origin and effect of myocardial function on the BEW in humans, have not been previously reported. Methods and Results—: Patients with single-vessel left anterior descending coronary disease and normal ventricular function (n=13) were recruited prospectively. We simultaneously measured LV function with a conductance catheter and derived wave intensity analysis using a pressure–low velocity guidewire at baseline and again 30 minutes after a 1-minute coronary balloon occlusion. The peak BEW correlated with the indices of diastolic LV function: LV dP/dtmin ( r s =−0.59; P =0.002) and τ ( r s =−0.59; P =0.002), but not with systolic function. In 12 patients with paired measurements 30 minutes post balloon occlusion, LV dP/dtmax decreased from 1437.1±163.9 to 1299.4±152.9 mm Hg/s (median difference, −110.4 [−183.3 to −70.4]; P =0.015) and τ increased from 48.3±7.4 to 52.4±7.9 ms (difference, 4.1 [1.3–6.9]; P =0.01), but basal average peak coronary flow velocity was unchanged, indicating LV stunning post balloon occlusion. However, the peak BEW amplitude decreased from −9.95±5.45 W·m –2 /s 2 ×10 5 to −7.52±5.00 W·m –2 /s 2 ×10 5 (difference 2.43×10 5 [0.20×10 5 to 4.67×10 5 ; P =0.04]). Conclusions—: Peak BEW assessed by coronary wave intensity analysis correlates with invasive indices of LV diastolic function and mirrors changes in LV diastolic function confirming the origin of the suction wave. This may have implications for physiological lesion assessment after percutaneous coronary intervention. Clinical Trial Registration—: URL:http://www.isrctn.org . Unique identifier: ISRCTN42864201.